Consumer perception towards corporate social responsibility on brand equity - Karpal Singh Dara Singh (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis, 2015)
The primary purpose of this study is to examine consumers' perception towards CSR and its effect on brand equity. This study investigates the drivers that motivate firms to adopt CSR and the effect of CSR dimensions on brand equity. The study also investigates the moderating effect of customer awareness and religiosity on the relationship between CSR and brand equity. In addition, the study also investigates the effect of brand equity (resulting from CSR practices) on consumer buying behaviour.